Sclerostin decreases in regular swimmers after ice swimming and is associated with meteorin-like protein serum levels - Mu, Shuai; Huang, Chongjun; Chen, Bobo; Zhao, Pengyu; Xu, Haoran; Zhang, Weihao; Dai, Huixu (Frontiers in Physiology, 2023)
Cold and exercise are two important stimuli affecting the secretion of osteokines and adipomyokines, which often occur simultaneously. However, few studies have investigated the changes in osteokines and adipomyokines induced by exercise during severe cold and their corresponding associations. Therefore, this study aimed to investigate the changes in sclerostin and meteorin-like (metrnl) protein before and after cold exercise (ice swimming [IS]) and observe their correlation. The data of 56 daily ice swimmers were included in this study. Serum sclerostin and metrnl were measured 30 min before IS and 30 min after. The fat mass, visceral fat area, fat-free mass, skeletal muscle mass, lumbar spine, and femoral neck bone mineral density of the ice swimmers were measured. After IS, sclerostin exhibited significant decreases, whereas metrnl showed no significant change. In addition, the baseline level of sclerostin and the decrease in sclerostin were positively correlated with serum metrnl after adjusting for age, gender, and body composition indicators. In conclusion, IS caused a significant decrease in sclerostin but did not affect metrnl. Furthermore, the associations between sclerostin and metrnl suggested a correlation between osteokines and adipomyokines; this encourages future exploration of the interconnection between bone, muscle, and fat, which will be beneficial for identifying potential common therapeutic targets for diseases such as osteoporosis, sarcopenia, and obesity.